Наедине с зарею: записки рыболова / Д. И. Струженцов - Струженцов Дмитрий Иванович (Лениздат, 1990)
Экземпляры: КХ (20080407) / Инвентарный номер: 965203 / Цена: 0.95 / Сис.шифр: 47.226 / Авт.знак: С 87 / ГРНТИ: 69 / ББК: 47.226